From the (Academic) middle to the top: an evaluation of the AVID/TOPS college access program. Issue 4 (2nd October 2018) - Kolbe, Tammy; Kinsley, Peter; Feldman, Rachel Carly; Goldrick-Rab, Sara
Abstract: Despite overall increases in college-going, college enrollment rates remain inequitable. Many programs attempt to address these persistent racial/ethnic and social class disparities in college attendance by intervening in the high school curriculum. Advancement Via Individual Determination (AVID) is among the longest standing and prevalent of these college access programs. In this paper, we present findings from a multi-year evaluation and cost analysis of the AVID/TOPS program – an enhanced AVID model – in place in Madison Metropolitan School District (Wisconsin). Taken together, the evaluation's findings characterize AVID/TOPS as a promising program model that is associated with an increased likelihood for college readiness and matriculation, particularly for student groups underrepresented in higher education. We also report on the resources and costs required to implement the program, and show that the program's benefits appear to exceed its costs.